KECEMASAN STATISTIK DITINJAU DARI JENIS KELAMIN - Suminta, Rini Risnawita; Sayekti, Fatma Puri (Pascasarjana IAIN Kudus, 2017)
The statistics course has always been one of the subjects of anxiety stressors for students who take the social sciences. Most students choose this subject of social sciences in order to avoid statistics or numeracy courses. Nevertheless students who take the social sciences must face a statistical course. This study aims to determine the differences of statistical anxiety in terms of gender. Respondents in this study are 66 students of Islamic Psychology course, Department of Ushuluddin, Sekolah Tinggi Agama Islam Negeri (STAIN) Kediri. The data collection techniques used in this study is a questionnaire in the form of scale. Statistics anxiety is the fear that occurs when a student working on a statistics course includes the collection, processing and interpretation of data. The results showed that there was a statistical anxiety difference between STAIN Kediri male and female students.